INDICATORS FOR SAFE URBAN TOURISM - Fauziah Che Leh, Norimah Rambeli @ Ramli, Baharudin Omar, Muhammad Yasin Harahap Arsalan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article provides a review of the indicators for safe urban tourism after evaluates the urban tourism concept which related to the tourism industry and the implementation of the safe city model towards the Malaysia urban area. This research uses the basic idea of a safe city model for proposing a conceptual framework in safe urban tourism. Content analysis is used to identify the principles indicators of safe urban tourism from the established literature, relevant reports and works. A theoretical framework of indicators for safe urban tourism was then formulated to be the main outcome of the study. The framework consists of a list of three groups (3) indicators of safe urban tourism which is (i) safe city factors, (ii) safe urban tourism factors and (iii) crime prevention strategies and step to be considered throughout the safe urban tourism development process. Given that research in safe urban tourism is still at its infancy and largely absent in the Malaysian context, this study aims to fill that research gap and contributes towards an existing scholarship. The theoretical framework is very useful to provide an essential guide to the stakeholders (Ministry of Tourism (MoT), Town and Country Planning Department and Kuala Lumpur City Hall) and researchers for formulating a clear guide of sustainability principles to be integrated into the development of future safe urban tourism in Malaysia.